Behavioural Response of Sitophilus zeamais to Essential Oil-Derived Compounds - Inês Sousa (14496491) (2025)
This file corresponds to the data presented in the paper entitled "Behavioural Response of Sitophilus zeamais (Coleoptera: Curculionidae) to Essential Oil-Derived Compounds", which recorded the time each insect (Sitophilus zeamais) spent in each of the 4-arm olfactometer zones (A, B and C), for a total of 10 minutes of observation. A, B, and C correspond to the near, central, and far zones, according to their position in relation to the tested essential oil-derived compound.